A Comparative Study of Rosa Montero and Zhang Jie’s Women’s Fiction of the 1970s - Lili, Shi (Sinología hispánica. China Studies Review, 2026)
This article focuses on analysing the novel Crónica del desamor by Spanish female writer Rosa Montero and the work The Ark by Chinese female writer Zhang Jie, using these two women's novels as examples for comparative study. The study is conducted from different perspectives in five points, namely, period background, writer's biography, novel study, female characters analysis and influence of works, comparing the similarities and differences in images of women, women's rights, women's status and women's consciousness between Spanish and Chinese women in the 1970s, and analysing the profound reasons behind them, in order to promote the understanding of women's literature in China and in Spain.